Aspek Legal Penguasaan Hutan oleh Mukim - Husin Taqwaddin (Universitas Syiah Kuala, 2010)
ABSTRACT: Mukim is one of the unique structure in Governance of Aceh, in which it is federation from several Gampong (village) which exist since Islam Religious lesson came to Aceh region. Therefore Mukim has long path story, it resulted authority and authority of Mukim in the past has already sufficient known and obeyed by the people who stayed in the Mukim area. Mukim has authority toward all of its territory, in the land and also in the sea. In the lagal aspect, Mukim since past until nowadays has the power basis or legal jurisdiction toward the Forrest in each Mukim area. The forrest exist in the Mukim area measured by the requirement go and back for a day, it is understood by the Mukim community as Uteun Mukim in which it is also called as rights of Kullah (Uteun Potallah). So terminology of Uteun Mukim is equivalent with Customary Forrest (hutan adat) in the Indonesia’s of national law. In the managerial aspect, in the Forrest management affair, the roles and responsibilities in the Mukim area are led by the customary chief of Forrest (Panglima Uteun or Pawang Glee). The management and using of the customary forest of Mukim almost always has coordination Imuem Mukim with Pawang Glee and also Petua Seunebok. Legal Aspect of the Forest Management by Mukim